Spiders (Arachnida: Araneae) in the semideciduous Atlantic Forest: An ecological and morphological trait dataset for functional studies - Munevar Lozano, Ana Katerinne (2020)
Background The semideciduous Atlantic Forest is one of the most diverse ecosystems in the world with a great diversity of spiders. Most spider-related studies in this ecosystem focused on species richness and composition; however, little is known about their trait diversity (including morphological, ecological and/or physiological traits). Two main datasets were compiled to generate a complete record of spider traits for this ecosystem. New information Here, we present two datasets about 259 species of spiders from the semideciduous Atlantic Forest of Argentina. The trait data set compiled information of morphological and ecological traits such as body size, femur length, ocular distance, foraging strategy, prey range, circadian activity and stratum preference; traits were assessed by species considering sexual dimorphism. The second dataset included information about phenology (season when spiders were collected), number of individuals assessed by species and presence/absence of spiders in the different sample sites. This dataset has high potential to help researchers in recording the state of a component of biodiversity (functional) and contributes with the study of ecosystem services and species conservation.